2022
DOI: 10.1167/jov.22.2.4
|View full text |Cite
|
Sign up to set email alerts
|

From photos to sketches - how humans and deep neural networks process objects across different levels of visual abstraction

Abstract: Line drawings convey meaning with just a few strokes. Despite strong simplifications, humans can recognize objects depicted in such abstracted images without effort. To what degree do deep convolutional neural networks (CNNs) mirror this human ability to generalize to abstracted object images? While CNNs trained on natural images have been shown to exhibit poor classification performance on drawings, other work has demonstrated highly similar latent representations in the networks for abstracted and natural im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…This suggests that object recognition can be resolved with the same amount of processing resources for different levels of visual abstraction of the image. This is consistent with previous computational work showing that representations for photographs and drawings at different levels of visual abstraction become highly similar when being processed in feedforward deep convolutional neural networks trained to categorize natural object images (Fan et al, 2018;Singer et al, 2022). While other work has demonstrated that additional recurrent processing is necessary for resolving degraded (Wyatte et al, 2012), occluded (Rajaei et al, 2019;Tang et al, 2018) or otherwise challenging images (Kar et al, 2019), our findings indicate that no additional mechanisms are needed for the robust recognition of abstract drawings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that object recognition can be resolved with the same amount of processing resources for different levels of visual abstraction of the image. This is consistent with previous computational work showing that representations for photographs and drawings at different levels of visual abstraction become highly similar when being processed in feedforward deep convolutional neural networks trained to categorize natural object images (Fan et al, 2018;Singer et al, 2022). While other work has demonstrated that additional recurrent processing is necessary for resolving degraded (Wyatte et al, 2012), occluded (Rajaei et al, 2019;Tang et al, 2018) or otherwise challenging images (Kar et al, 2019), our findings indicate that no additional mechanisms are needed for the robust recognition of abstract drawings.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, photos and drawings showed the highest RDM correlation (r=0.79) while the correlation for photos and sketches (r=0.41) as well as the correlation between drawings and sketches (r=0.45) were lower. Next, to confirm that human subjects perceive the object images in the different types of depiction similarly at a conceptual level, we used previously acquired data (Singer et al, 2022) where workers on Amazon Mechanical Turk indicated which of three object images they thought was the odd-one out (Hebart et al, 2020). These triplet judgments were used to construct perceptual similarity matrices for each type of depiction separately, which we subsequently correlated to each other to estimate their representational similarity.…”
Section: Natural Object Images and Line Drawings Differ In Low-level ...mentioning
confidence: 99%
“…This suggests that object recognition can be resolved with the same amount of processing resources for different levels of visual abstraction of the image. This is consistent with previous computational work showing that representations for photographs and drawings at different levels of visual abstraction become highly similar when being processed in feedforward deep convolutional neural networks trained to categorize natural object images ( Fan et al, 2018 ; Singer et al, 2022 ). While other work has demonstrated that additional recurrent processing is necessary for resolving degraded ( Wyatte et al, 2012 ), occluded ( Tang et al, 2018 ; Rajaei et al, 2019 ), or otherwise challenging images ( Kar et al, 2019 ), our findings indicate that no additional mechanisms are needed for the robust recognition of abstract drawings.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, photographs and drawings showed the highest RDM correlation ( r = 0.79) while the correlation for photographs and sketches ( r = 0.41) as well as the correlation between drawings and sketches ( r = 0.45) were lower. Next, to confirm that human subjects perceive the object images in the different types of depiction similarly at a conceptual level, we used previously acquired data ( Singer et al, 2022 ) where workers on Amazon Mechanical Turk indicated which of three object images they thought was the odd-one-out ( Hebart et al, 2020 ). These triplet judgments were used to construct perceptual similarity matrices for each type of depiction separately, which we subsequently correlated to each other to estimate their representational similarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation